Self-Reflection and Math Performance in an Online Learning Environment - Choi, Jinnie; Walters, Alyssa; Hoge, Pat (Online Learning, 2017)
According to recent reports, K-12 full-time virtual school students have shown lower performance in math than their counterparts in regular brick-and-mortar schools. However, research is lacking in what kind of programmatic interventions virtual schools might be particularly well-suited to provide to improve math learning. Engaging students in self-reflection is a potentially promising pedagogical approach for supporting math learning. Nonetheless, it is unclear how models for math learning in regular classrooms translate in an online environment. The purpose of this study was to (a) analyze rich assessment data from virtual schools to explore the association between self-reflection and math performance, (b) compare the patterns found in student self-reflection across elementary, middle, and high school levels, and (c) examine whether providing opportunities for self-reflection had positive impact on learning in a virtual learning environment. In this study, the self-reflection assessments were developed and administered multiple times within several math courses during the 2014-2015 school year. These assessments included 4-7 questions that ask students to reflect on their understanding of the knowledge and skills they learned in the preceding lessons and units. Using these assessments, multiple constructs and indicators were measured, which include confidence about the topic knowledge/understanding, general feelings towards math, accuracy of self-judgment against actual test performance, and frequency of self-reflection. Through a series of three retrospective studies, data were collected from full-time virtual school students who took three math courses (one elementary, one middle, and one high school math course) in eight virtual schools in the United States during the 2013-2014 and 2014-2015 school years. The results showed that (a) participation in self-reflection varied by grade, unit test performance level, and course/topic difficulty; (b) more frequent participation in self-reflection and higher self-confidence level were associated with higher final course performance; and (c) self-reflection, as was implemented here, showed limited impact for more difficult topics, higher grade courses, and higher performing students. Implications for future research are provided.